Maximum-scoring path sets on pangenome graphs of constant treewidth - Brejová, Broňa; Gagie, Travis; Herencsárová, Eva; Vinař, Tomáš (Frontiers in Bioinformatics, 2024)
We generalize a problem of finding maximum-scoring segment sets, previously studied by Cs űr ös ( 2004), from sequences to graphs. Namely, given a vertex-weighted graph G and a non-negative startup penalty c, we can find a set of vertex-disjoint paths in G with maximum total score when each path's score is its vertices' total weight minus c. We call this new problem maximum-scoring path sets (MSPS). We present an algorithm that has a linear-time complexity for graphs with a constant treewidth. Generalization from sequences to graphs allows the algorithm to be used on pangenome graphs representing several related genomes and can be seen as a common abstraction for several biological problems on pangenomes, including searching for CpG islands, ChIP-seq data analysis, analysis of region enrichment for functional elements, or simple chaining problems.